IT’S YOUR TURN, OFFICER!: THE INP’S NEW VISIBILITY THROUGH SOCIAL MEDIA (CASE STUDY OF EVANS’ BRIMOB FACEBOOK STATUS) - Andi Windah (SOSIOLOGI: Jurnal Ilmiah Kajian Ilmu Sosial dan Budaya, 2017)
History has proved that police have always had opposing view regarding sharing and disseminating information to the public, especially when their state of reputation, legitimacy and accountability are taken into account. Undoubtedly, media have always played important parts in the hurdle. The presence of media is inseparable with police institution, including the current media technologies, social media. The same condition also applies to The Indonesian National Police (INP) with the case of Evans BRIMOB Facebook’s status. The case is believed to present a new type of visibility to the INP’s institution. Utilizing documentary analysis as well as literature review as main methods in studying the case, this article aims to identify on how the case alter of the INP’s visibility and Facebook’s contribution during the process. Using the new visibility consept offered by Thompson, it is found that, Evans’s status had raised the INP’s visibility by exposing the exemplary of its member improper manner. Meanwhile, Facebook has lifted the INP’s visibility by facilitating greater exposure over the INP’s inadvertent performance. In conclusion, the case has alter not only the INP’s visibility to its public but also reinforce the institution to adopt Facebook as one of its information sharing platforms.